Evaluation of microbial‐fructo‐oligosaccharides metabolism by human gut microbiota fermentation as compared to commercial inulin‐derived oligosaccharides - Roupar, Dalila (2022)
The prebiotic potential of fructo‐oligosaccharides (microbial‐FOS) produced by a newly isolated Aspergillus ibericus, and purified by Saccharomyces cerevisiae YIL162 W, was evaluated. Their chemical structure and functionality were compared to a non‐microbial commercial FOS sample. Prebiotics were fermented in vitro by fecal microbiota of five healthy volunteers. Microbial‐FOS significantly stimulated the growth of Bifidobacterium probiotic strains, triggering a beneficial effect on gut microbiota composition. A higher amount of total short‐chain fatty acids (SCFA) was produced by microbial‐FOS fermentation as compared to commercial‐FOS, particularly propionate and butyrate. Inulin neoseries oligosaccharides, with a degree of polymerization (DP) up to 5 (e.g., ne-okestose and neonystose), were identified only in the microbial‐FOS mixture. More than 10% of the microbial‐oligosaccharides showed a DP higher than 5. Differences identified in the structures of the FOS samples may explain their different functionalities. Results indicate that microbial‐FOS exhibit promising potential as nutraceutical ingredients for positive gut microbiota modulation.